Risk of hospital admission with coronavirus disease 2019 in healthcare workers and their households: nationwide linkage cohort study. (28th October 2020) - Shah, Anoop S V; Wood, Rachael; Gribben, Ciara; Caldwell, David; Bishop, Jennifer; Weir, Amanda; Kennedy, Sharon; Reid, Martin; Smith-Palmer, Alison; Goldberg, David; McMenamin, Jim; Fischbacher, Colin; et al.
Abstract: Objective: To assess the risk of hospital admission for coronavirus disease 2019 (covid-19) among patient facing and non-patient facing healthcare workers and their household members. Design: Nationwide linkage cohort study. Setting: Scotland, UK, 1 March to 6 June 2020. Participants: Healthcare workers aged 18-65 years, their households, and other members of the general population. Main outcome measure: Admission to hospital with covid-19. Results: The cohort comprised 158 445 healthcare workers, most of them (90 733; 57.3%) being patient facing, and 229 905 household members. Of all hospital admissions for covid-19 in the working age population (18-65 year olds), 17.2% (360/2097) were in healthcare workers or their households. After adjustment for age, sex, ethnicity, socioeconomic deprivation, and comorbidity, the risk of admission due to covid-19 in non-patient facing healthcare workers and their households was similar to the risk in the general population (hazard ratio 0.81 (95% confidence interval 0.52 to 1.26) and 0.86 (0.49 to 1.51), respectively). In models adjusting for the same covariates, however, patient facing healthcare workers, compared with non-patient facing healthcare workers, were at higher risk (hazard ratio 3.30, 2.13 to 5.13), as were household members of patient facing healthcare workers (1.79, 1.10 to 2.91). After sub-division of patient facing healthcare workers into those who worked in "front door, " intensive care, and non-intensive care aerosol generating settings and other, those in front door roles were at higher risk (hazard ratio 2.09, 1.49 to 2.94). For most patient facing healthcare workers and their households, the estimated absolute risk of hospital admission with covid-19 was less than 0.5%, but it was 1% and above in older men with comorbidity. Conclusions: Healthcare workers and their households contributed a sixth of covid-19 cases admitted to hospital. Although the absolute risk of admission was low overall, patient facing healthcare workers and their household members had threefold and twofold increased risks of admission with covid-19.